ESTIMATION OF PROTECTION FACTORS FOR SURROGATE VEHICLE MODELS IN ENVIRONMENTAL CONTAMINATION SCENARIOS. Issue 20 (1st November 2022) - Dalak, Sena; Asano, Ethan; Dewji, Shaheen
Abstract: In the event of a nuclear or radiological incident involving the release of radioactive material, it may be critical to estimate doses to individuals who are transported through contaminated areas by vehicles. The radiation protection factor (RPF) for vehicles can be calculated to determine the level of shielding protection by the vehicle from external radiation sources. Prior studies evaluating RPFs demonstrate a lack of realistic vehicle configurations and the results cannot be extended directly to scenarios where a vehicle is surrounded by a contaminated environmental field. In this work, sex-averaged effective dose-rate coefficients were computed employing International Commission on Radiological Protection Publication 103 recommendations for radionuclides of interest and used to calculate the RPF as the ratio of unshielded to shielded dose for various radionuclides of interest in consequence management scenarios. Comparisons to dose reduction factors calculated using environmental measurement data from the 2011 Fukushima Daiichi nuclear incident were conducted to benchmark to experimental field measurements.